Konstantinos Gardikas: German Connections of a Greek Criminologist and Liberal Politician in the Interwar Period - Georgoulas, Stratos (Zeitschrift für Balkanologie, 2014)
Konstantinos Gardikas has been the most prominent figure in Greek criminology and a well-known politician both during the interwar period and after (till 1968). In contrast with his reputation as a liberal scientist, his unknown published work in the German journal Monatsschrift für Kriminalpsychologie und Strafrechtsreform, during 1934–35 place him in a network dominated by Kriminalbiologische Gesellschaft (established by Franz Exner, a key figure in German criminology during the interwar period, a member of National Socialist union of lawyers, and director of the book series “The Biology of Crime in the New Reich”), which applied a Nazist ideology to the penal and criminological area. Using a universal scientific language, Gardikas tried to implement a part of this ideology in the Greek context, both through his dominant position in academia and his political position as the person in charge of the forensic department of Greek police for over 40 years.